VEHICLE DETECTION USING HAAR CASCADE - Sagar Chinchorkar; Manoj Silag; Vaibhav Najan (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Vehicle detection is an important part of traffic inspection system. In this paper we outline a vehicle detection technique which could be used in vehicle inspection system. An intelligent vehicle inspection system uses an advance features with electronic devices which are used for analysis the traffic problem. So the first step is to detect the vehicle.The system uses Haar like feature- cascading technology.Its a machine learning technology which uses positive and negative images for training purpose.